Construction and application of a multi-objective rolling horizon optimization mathematical model in intelligent dispatching for telecom operators - LI Fang; MA Xiaoliang; LIU Ying; LI Yuan; XIN Sheng (Dianxin kexue)
With the rapid development of the telecommunications industry, intelligent dispatching has become a key means of enhancing service quality and efficiency for operators. However, traditional dispatching methods struggle to simultaneously meet the multiple demands of operators for service efficiency and quality. A mathematical model based on multi-objective optimization was proposed, which was set with three objectives: total expected customer satisfaction score, work order response time, and agent workload balance. Additionally, an adaptive multi-objective optimization algorithm was designed, incorporating techniques such as adaptive weight adjustment, multi-objective optimization, and rolling horizon optimization to solve the multi-objective optimization model. Experimental results from a provincial telecom operator's agent system demonstrate that the model can improve both the service efficiency and service quality of telecom operators.